Enhancing English proficiency through subtitled movies: A study at an Islamic junior high school in Aceh - Itawari, Cut; Nisa, Rahmatun; Safura, Siti (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2025)
The influence of employing movie subtitles as a teaching technique for English is examined in this study, with an emphasis on how subtitles help students become more proficient in the language. In light of the potential advantages of incorporating multimedia into the classroom, the study investigated how well English-subtitled films might improve students' understanding and involvement. A sample of 14 seventh-grade students from an Islamic junior high school in Aceh Besar, Aceh Province, participated in the study, which used a quantitative research approach. Tests and questionnaires were used to gather information in order to assess students’ perceptions and progress. As demonstrated by a noticeable difference in performance before and after implementation, the results showed that incorporating movie subtitles greatly enhanced students' competence of English. This is evident from the pre-test and post-test scores, which showed a statistically significant improvement after the use of English-subtitled movies. Strong favorable feedback was also noted in the questionnaire responses, with the majority of students concurring that English movie subtitles in language instruction greatly facilitates students' comprehension in learning English.